LIFE-SPACE MOBILITY IN THE CANADIAN LONGITUDINAL STUDY ON AGING: A MULTI-DISCIPLINARY PERSPECTIVE. (11th November 2018) - Kuspinar, A; Verschoor, C; Beauchamp, M; Gregory, M; Richardson, J; Vrkljan, B
Abstract: Factors that may hinder or support the independent life-space mobility of older adults are complex and multi-factorial. However, existing studies have focused on a narrow group of factors that are often discipline specific (i.e. biomechanics, biological, etc.). A multi-disciplinary and comprehensive assessment of life-space mobility is needed to optimize opportunities for healthy aging and prevent mobility decline in older adults. As such, the purpose of this study was to examine how biological, psychosocial, physical, cognitive, environmental, and financial factors influence life space mobility in a large population-based sample of community dwelling older adults. For this, we employed the Canadian Longitudinal Study on Aging (CLSA) baseline comprehensive dataset version 3.2, that includes performance-based testing and in-depth questionnaires on more than 30, 000 adults aged 45–85. Multivariate regression was carried out to identify variables that were significantly associated with the Life-Space Index (LSI). Analyses were adjusted for age, sex, culture and the presence of chronic conditions. The sample was 51% women, with a mean age of 63 years and mean LSI score of 90 (range 24 to 120). Physical (4-Meter Timed Walk Test Beta (ß)=-2.2 and lung function ß=1.3), psychosocial (depression ß=-0.5, social support ß=2.3), cognitive (ß=0.6), environmental (urban vs. rural ß=8.8) and financial (income ß=9.6) factors were significantly associated with the LSI when adjusted for covariates. This study demonstrated that determinants of life-space mobility are multi-factorial and span several disciplines. Validation of these results with longitudinal data may provide insight into management strategies for preserving life-space mobility.